Report of the Working Group on the Assessment of Pandalus ... - ICES (ICES Expert Group reports (until 2018), 2023)
The Working Group on the Assessment of Pandalus Stocks (Chairman: Mr S. MunchPetersen, Denmark) met at ICES Headquarters from 11-14 February 1991 (C.Res. 1990{2:5:1) to assess the status of stocks of Pandalus borealis in the North Sea, Skagerrak, and Kattegat. ...